DYNAMICS OF CRIMINAL LAW - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Review of the monograph of Balobanova D.O. "Dynamics of criminal law (doctrinal provisions)".